Berberine protects steatotic donor undergoing liver transplantation via inhibiting endoplasmic reticulum stress-mediated reticulophagy. Issue 18 (December 2019) - Zhang, Nan; Sheng, Mingwei; Wu, Man; Zhang, Xinyue; Ding, Yijie; Lin, Yuanbang; Yu, Wenli; Wang, Shusen; Du, Hongyin
Steatotic livers are more susceptible to ischemia/reperfusion injury, and increase the risk of primary graft non-function after liver transplantation. The protective effects of berberine have been described in various liver pathological models. However, it is unknown if berberine exerts its beneficial action in steatotic donors undergoing liver transplantation. In the present study, male Wistar rats were fed with high-fat diet (HFD) for 12 weeks to induce moderate steatotic liver. Then orthotropic liver transplantation was constructed. Berberine (200 mg/kg/d) was given intragastrically one week before liver transplantation. Thapsigargin (TG) (0.2 mg/kg) was administrated intravenously 24 h before liver transplantation. Liver function, oxidative stress, and inflammatory cytokine were detected by biochemical or histopathological analysis. The morphology of autophagosomes and endoplasmic reticulum (ER) was observed by transmission electron microscopy. The expression of CHOP, BIP, the phosphorylation of PERK, LC3-II/I, Beclin-1, and p62 were determined by Western blot assay. The co-localization of endoplasmic reticulum marker (KDEL) and autophagic protein (LC3B) was analyzed by immunofluorescence microscopy. The level of reticulophagy hallmark (FAM134B) was determined by immunohistochemistry. Compared with HFD + LT group, berberine ameliorated hepatocellular damage, decreased the oxidative stress level and inflammatory cytokine release. Simultaneously, berberine inhibited the expression of both endoplasmic reticulum stress parameters and autophagy-related proteins. Additionally, the co-localization of endoplasmic reticulum marker and LC3B was also reduced in HFD + BBR + LT group. berberine down-regulated the level of FAM134B. TG reversed the beneficial effects of berberine. Our study revealed that berberine exerts protective effects on steatotic livers undergoing transplantation by inhibiting endoplasmic reticulum stress-mediated reticulophagy. Impact statement: Berberine is isolated from traditional Chinese medicine plants and has dramatically therapeutic potential against inflammation, diarrhea, and diabetes. But the benefits of BBR on steatotic grafts after liver transplantation remain poorly understood. Our findings might help explain the mechanism of berberine in protecting steatotic livers undergoing transplantation and give advantageous insights that berberine has potential as a suitable candidate for preventing hepatic injury after steatotic liver transplantation by inhibiting ER stress-mediated reticulophagy.